Surface Chemical Functionalization to Achieve Extreme Levels of Molecular Confinement in Hybrid Nanocomposites. (17th June 2019) - Wang, Can; Isaacson, Scott G.; Wang, Yucheng; Lionti, Krystelle; Volksen, Willi; Magbitang, Teddie P.; Chowdhury, Mithun; Priestley, Rodney D.; Dubois, Geraud; Dauskardt, Reinhold H.
Abstract: Polymer confinement is realized in hybrid nanocomposites where individual polymer molecules are confined by a nanoporous matrix to dimensions less than the molecular size of the polymer. Here it is shown that by functionalizing the interior pore surfaces of a nanoporous organosilicate matrix, the pores can be filled with polystyrene molecules to achieve extreme levels of molecular confinement not previously possible. This provides opportunities for unique thermal and mechanical properties. It is shown that pore surface functionalization markedly impacts the polymer mobility during polymer infiltration by affecting the polymer–pore surface interaction, addressing the challenge of filling high‐molecular‐weight polymer molecules into nanoscale‐confined spaces. This allows for achieving extreme levels of molecular confinement with the loss of interchain entanglement and extensive polymer elongation along the pore axis. The glass transition temperature of the polymer is suppressed compared to bulk polymer melt, and is significantly affected by the polymer–surface interaction, which changes the polymer segmental mobility. The polymer–surface interaction also affects the interfacial polymer–pore sliding shear stress during polymer pullout from the nanopores, markedly affecting the fracture resistance of the nanocomposite. Abstract : Molecular confinement of polymers by a nanoporous matrix is achieved in hybrid nanocomposites. The interaction of the confined polymer with the pore surface can be manipulated by surface chemical functionalization of the pores to significantly influence the polymer mobility and the nanocomposite thermal and mechanical properties, allowing achievement of extreme levels of molecular confinement not previously possible.